ANTIHEPATITIS C VIRUS ACTIVITY OF INDONESIAN MAHOGANY (TOONA SURENI) - Hafid, Achmad Fuad; Wahyuni, Tutik Sri; Tumewu, Lidya; Apryani, Evhy; Permanasari, Adita Ayu; Adianti, Myrna; Aoki Utsubo, Chie; Widyawaruyanti, Aty; Inge Lusida, Maria; Soetjipto, Soetjipto; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Toona sureni (Indonesian mahogany) is a member of Meliaceae family and locally known as suren. Previous study reported that T. sureni leaves extract exhibited antiviral activity with 50% inhibitory concentration (IC50) value of 13.9 Â± 1.6 Î¼g/ml against hepatitis C virus (HCV) J6/JFH1. Cytotoxicity analysis of T. sureni leaves extract did not reveal any cytotoxicity effect; therefore, further study was taken to investigate the active substances from the extract. Methods: Bioassay-guided isolation of anti-HCV was conducted using Huh-7.5 cells infected with HCV J6/JFH1 in the presence of extracts, fractions, or compounds from the plant. Results: Ethyl acetate fraction (Fr E) exhibited high anti-HCV activity with IC50 value of 1.7 Î¼g/ml. Further, separation of Fr E by open column chromatography resulted in nine sub-fractions (sub-Fr E1-E9). Sub-Fr E3 and E4 have IC50 value of 29.90 Î¼g/ml and 7.68 Î¼g/ml, respectively. Polyphenols compounds have been isolated from sub-Fr E3 and E4. The structures have been determined to be ethyl gallate (1), methyl gallate (2), catechin (3), gallic acid (4), and quercetin 3-O-rhamnoside (5). Among the isolated compounds, gallic acid showed to possess strong anti-HCV activity with IC50 value of 15.9 Î¼g/ml. Conclusion: T. sureni and its isolated compound, gallic acid, may be good candidates to develop for alternative and/or complementary agents of anti-HCV infection.